2023
DOI: 10.24272/j.issn.2095-8137.2023.003
|View full text |Cite
|
Sign up to set email alerts
|

Probing the processing of facial expressions in monkeys via time perception and eye tracking

Abstract: Accurately recognizing facial expressions is essential for effective social interactions. Non-human primates (NHPs) are widely used in the study of the neural mechanisms underpinning facial expression processing, yet it remains unclear how well monkeys can recognize the facial expressions of other species such as humans. In this study, we systematically investigated how monkeys process the facial expressions of conspecifics and humans using eye-tracking technology and sophisticated behavioral tasks, namely the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The fact that different states are associated with distinct constellations of facial features points to a role of facial expressions beyond emotional expression. Facial expressions have so far been mostly studied in a social or emotional context, and mostly in social species such as monkeys (28, 61) and humans (25, 62). In mice, until recently facial expressions were thought to mainly reflect pain (29, 63, 64), until careful analyses using machine-learning algorithms identified their facial expressions as innate and accurate reflections of several emotional states as well (22, 31, 65).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that different states are associated with distinct constellations of facial features points to a role of facial expressions beyond emotional expression. Facial expressions have so far been mostly studied in a social or emotional context, and mostly in social species such as monkeys (28, 61) and humans (25, 62). In mice, until recently facial expressions were thought to mainly reflect pain (29, 63, 64), until careful analyses using machine-learning algorithms identified their facial expressions as innate and accurate reflections of several emotional states as well (22, 31, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Animal behavior is critically related to neural activity, neurological function, and cognitive states. Research has uncovered the mechanisms that govern a variety of complex animal behaviors, including those related to feeding ( Shafiullah et al, 2019 ), anxiety, and mating ( Moulin et al, 2021 ), as well as the analysis of daily behaviors ( Liu et al, 2022 ) and recognition of behaviors based on facial expressions ( Liu et al, 2023 ). However, the core problem lies in the extraction of meaningful information from the wealth of data on animal behavior within the context of neuroscience, propelled by advancements in experimental techniques ( Bath et al, 2014 ; Scaplen et al, 2019 ; Svensson et al, 2018 ).…”
Section: Ai In Animal Behaviormentioning
confidence: 99%
“…For instance, Nadal-Nicolás et al ( 2023 ) thoroughly reviewed and analyzed the specificity of nine markers for the unambiguous identification of all or most RGCs (i.e., pan-RGC markers), a crucial prerequisite for studying their degeneration and neuroprotection, across rats, mice, and macaques. Liu et al ( 2023 ) revealed that monkeys show heightened sensitivity to the facial expressions of conspecifics compared to those of humans, offering new insights into inter-species communication. Li et al ( 2023 ) presented a comprehensive analysis of the genetic and physiological attributes critical for the sustained expansion of undifferentiated spermatogonial stem cells in tree shrews and proposed an effective strategy for extended in vitro maintenance.…”
mentioning
confidence: 99%